2017
DOI: 10.21273/horttech03705-17
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Hazelnut Cultivars from Oregon, Italy, and Spain, in Northeastern Spain

Abstract: Eleven hazelnut (Corylus avellana) cultivars, four Spanish (Clon La Masó, Negret N-9, Negret Primerenc, and Pauetet), four Italian (San Giovanni, Tonda Italiana, Tonda di Giffoni, and Tonda Romana), and three cultivars from Oregon State University’s (OSU) breeding program (Clark, Lewis, and Willamette), were evaluated in northeastern Spain over a period of 15 years (2001–14). The trial was planted at the Institute of Agriculture and Food Research and Technology (IRTA)-Mas de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Simulated average yield ranges between 0 and 3.7 kg plant − 1 over the study area, with a standard deviation of 1.9 kg plant − 1 for the recent past climate. These values are in line with experimental data measured in varietal trials conducted with the 'Tonda di Giffoni' cultivar in Spain and southeastern Australia, where hazelnut yields were 3.5 kg plant − 1 and 2.2-4.7 kg plant − 1 respectively (Baldwin, 2010;Baldwin et al, 2003;Rovira et al, 2017). In addition, the areas where simulated yield is above 1.5 kg plant − 1 (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Simulated average yield ranges between 0 and 3.7 kg plant − 1 over the study area, with a standard deviation of 1.9 kg plant − 1 for the recent past climate. These values are in line with experimental data measured in varietal trials conducted with the 'Tonda di Giffoni' cultivar in Spain and southeastern Australia, where hazelnut yields were 3.5 kg plant − 1 and 2.2-4.7 kg plant − 1 respectively (Baldwin, 2010;Baldwin et al, 2003;Rovira et al, 2017). In addition, the areas where simulated yield is above 1.5 kg plant − 1 (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, in the current review, the results showed different results, mainly, the highest oil concentration is observed in countries with a warm climate (Spain), while under the Turkish and Iranian climate, the lowest oil concentration was obtained, which is consistent with previous results-despite the lack of direct evidence for the relationships between temperature and kernel oil concentration in hazelnuts. Rovira et al [50] observed no differences of protein and mineral content between the cultivars, whereas Hosseinpour et al [15] presented significant variation in the kernel composition, which depended on the hazelnut cultivar. Hoekstra et al [60] showed that in plants tolerant to water stress, compatible solutes are bound to protein surfaces, thus stabilizing the native protein structure, whereas in plants sensitive to such deficiency, the proteins tend to degrade.…”
Section: Nutritional Valuementioning
confidence: 96%
“…In the case of other cultivars' kernel ratio, they are comparable between 41 and 47%. Despite the fact, in most of the cited studies, the data of morphological traits are averaged [34,41,50,54] or from only one year of harvest [9,15,25], what could create limitations in the observation of seasonal changes in hazelnut cultivars.…”
Section: Cultivars Morphological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different standards to measure hazelnuts' quality in terms of dimensions, aspect, and hidden defects [10]. Furthermore, hazelnut properties vary according to the cultivar [11]. Knowledge of hazelnuts' physical and chemical properties is crucial as they are necessary to determine numerous parameters of extreme importance to guarantee the quality of the product.…”
Section: Introductionmentioning
confidence: 99%